2020
DOI: 10.1186/s12931-020-01448-3
|View full text |Cite
|
Sign up to set email alerts
|

The sputum microbiome is distinct between COPD and health, independent of smoking history

Abstract: Background: Airway bacterial dysbiosis is a feature of chronic obstructive pulmonary disease (COPD). However, there is limited comparative data of the lung microbiome between healthy smokers, non-smokers and COPD. Methods: We compared the 16S rRNA gene-based sputum microbiome generated from pair-ended Illumina sequencing of 124 healthy subjects (28 smokers and 96 non-smokers with normal lung function), with single stable samples from 218 COPD subjects collected from three UK clinical centres as part of the COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 33 publications
10
59
0
1
Order By: Relevance
“…The abundance of Moraxella is considered to have a significant positive correlation with the percentage of sputum neutrophils (1). High proportions of Prevotella, Veillonella, and Actinomyces species have been observed in COPD and healthy people, but the difference is not significant (3,32); our research is consistent with this finding. The occurrence of COPD exacerbation events may be related to the reduction in microbiome diversity and increased proportion of Proteobacteria (33,34).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The abundance of Moraxella is considered to have a significant positive correlation with the percentage of sputum neutrophils (1). High proportions of Prevotella, Veillonella, and Actinomyces species have been observed in COPD and healthy people, but the difference is not significant (3,32); our research is consistent with this finding. The occurrence of COPD exacerbation events may be related to the reduction in microbiome diversity and increased proportion of Proteobacteria (33,34).…”
Section: Discussionsupporting
confidence: 88%
“…Chronic obstructive pulmonary disease (COPD) is a common respiratory disease that is characterized by persistent symptoms and impaired lung function due to small airway obliteration and alveolar destruction and is related to a chronic inflammatory response in the lungs (1,2). The exacerbation of airway inflammation and disease progression during acute exacerbation of COPD have been demonstrated to be related to changes in the lung microbiology (3). The effects of acute exacerbation of COPD on airway microbiology mainly consist of the imbalance of airway microbiology and changes in microecological diversity (1,3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that higher ICS doses are significantly associated with greater total airway bacterial load [ 4 , 7 ], but we did not see a difference in ICS use between groups, perhaps due to the high overall ICS use. Some patients were current smokers (34%); a previous analysis of the COPDMAP data reports no difference in microbiome between smoking and non-smoking individuals [ 42 ]. We were unable to determine if any changes in colonisation status were affected by antibiotics or prior vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…being more common than Bacteroides ( Prevotella spp.) being significantly reduced ( Einarsson et al 2016 ; Haldar et al 2020 ). In addition, in stable COPD, a higher level of colonization with potentially pathogenic bacteria, such as H. influenzae, S. pneumonia , and M. catarrhalis is associated with a greater chance of exacerbation and a more severe airflow obstruction ( Martinez et al 2013 ; Ditz et al 2020 ).…”
Section: Airway Microbiome In Chronic Obstructive Pulmonary Disease (mentioning
confidence: 99%